A multicriteria method to identify and rank IEQ criticalities: Measurements and applications for existing school buildings - Francesco Leccese; Michele Rocca; Giacomo Salvadori; Elisa Belloni; Cinzia Buratti (Energy and Built Environment)
This study proposes a method to obtain a ranking of the critical issues related to Indoor Environmental Quality (IEQ)in existing school buildings. A multi-criteria method for a comprehensive evaluation of IEQ in school buildings is described and discussed. The method includes data collection, field measurements, and subjective investigations. The novelty of the study does not lie in the single stages of which the method is composed (for example in the phase involving field measurements, there are consolidated procedures in the technical and scientific literature to conduct them), but rather in the collection and rationalization of a complete and articulated assessment process that can guide the technicians and managers in the decision making. To show the whole proposed evaluation method, the case study of the university classrooms of the School of Engineering of Pisa was studied. From the application of the evaluation method to the case study, a rank of the IEQ critical issues observed and a rank of the most IEQ critical environments was therefore obtained. The study also focused on the impact of weighting schemes of the IEQ assessment results. Then the results of the case study were discussed by evaluating the impact of alternative weighing schemes present in the scientific literature. The discussion shows that to identify the most critical environmental factors, the choice of the weighting scheme is extremely important although the greatest weight does not always correspond to the most critical environmental factor. The presented results can interest not only technical personnel involved in IEQ assessments and interventions for its improvement, but also researchers investigating IEQ that intend to compare methodologies and weighting schemes.